Postcoloniality and History - Dirlik, Arif (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2006)
AbstractThis essay explores the implications of postcolonial writing for our understanding of the practice of history. It outlines the central principles of contemporary postcolonial inquiry, and provides a critique of recent trends in the field. With its pre-occupation with the local and the particular, contemporary postcolonial writing has become detached from the critical frameworks of analysis embodied in the initial phase of postcolonial writing.